A study on the association between the oral health knowledge, oral hygiene practices and dental health status of Mothers and Children in the Scandinavian's Children mission at Barangay Silangan, Quezon city - Capistrano, Vanessa Gela B.
Mothers have great influence on the development of the behavior of growing children. They serve as guides which their children mimic. Therefore, it is likely to expect that both mother and child have similarities in terms of character. This study aimed to determine the association between the oral health knowledge, oral hygiene practices and dental health status of mothers and their children. Fifty four children who are currently enrolled in the Scandinavian's Children School Mission, and their respective mothers were chosen to participate in the study (n=54). Total enumeration was used because the researchers opted to include all the children attending the day care center to have a sufficient sample population. The respondents were asked to answer a questionnaire and were subjected to an oral examination and an interview afterwards. The questionnaire was comprised of nine items for children and six items for mothers. This is used to assess the oral hygiene practices of the respondents. An oral examination was conducted with the use of DMFT/dmft index to evaluate the dental health status of both mothers and children. The respondents were interviewed afterwards using interview guide composed of four questions for children and eight questions for mothers. The relationships of each component were determined using a cross-sectional analysis, which were then subjected to Chi-square test of association. The test showed that eight out of the nine paired categories showed a chi-square of lesser than the critical value, which leads to the rejection of the research hypothesis. Based on the results, the researchers concluded that there is no association between the oral health knowledge, oral hygiene practices and oral health status of mothers and children.